1994
DOI: 10.1172/jci117430
|View full text |Cite
|
Sign up to set email alerts
|

C5a-induced expression of P-selectin in endothelial cells.

Abstract: Human umbilical vein endothelial cells have recently been shown to respond to C5a with increases in intracellular Ca2", production of D-myo-inositol 1,4,5-triphosphate and superoxide anion generation. In the current studies, C5a has been found to cause in a time-and dose-dependent manner rapid expression of endothelial P-selectin, secretion of von Willebrand factor, and adhesiveness for human neutrophils. The effects of C5a in P-selectin expression and adhesiveness of neutrophils were similar to the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
273
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(298 citation statements)
references
References 43 publications
9
273
0
7
Order By: Relevance
“…Although many other inflammatory pathways can lead to neutrophil priming and chemotaxis, virtually no neutrophils were seen in the fB Ϫ/Ϫ group, demonstrating that these other pathways are not playing a significant role in neutrophil recruitment in this model. Complement activation has been shown to increase expression of the adhesion molecules P-selectin, Eselectin, and ICAM-1 (31,32). By increasing expression of these adhesion molecules, complement activation may initiate neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Although many other inflammatory pathways can lead to neutrophil priming and chemotaxis, virtually no neutrophils were seen in the fB Ϫ/Ϫ group, demonstrating that these other pathways are not playing a significant role in neutrophil recruitment in this model. Complement activation has been shown to increase expression of the adhesion molecules P-selectin, Eselectin, and ICAM-1 (31,32). By increasing expression of these adhesion molecules, complement activation may initiate neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…This injury has been attributed to biological effects of C5a and MAC. C5aR has been localized by immunohistology on bronchial and alveolar epithelial cells as well as vascular smooth muscle and endothelial cells of human lung tissue (26,28,57,58). The potential for tissue activation through the C5aR has been verified for endothelial cells in culture.…”
Section: Figurementioning
confidence: 98%
“…The potential for tissue activation through the C5aR has been verified for endothelial cells in culture. Foreman and colleagues (28) found that C5a could activate endothelial cells directly through C5aR and that this activation was augmented in the presence of TNF-␣. Using C5aR knockout mice, Hopken et al (59) have demonstrated a dominant role for the C5aR in the lung, but only a synergistic role together with other inflammatory mediators in immune complex-mediated peritonitis and skin injury.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…These two receptors belong to the seven-transmembrane receptor superfamily and are coupled to a G i protein (2,3). C3aR and C5aR are expressed in myeloid cells (4 -8) and, more surprisingly, in non-myeloid cells and tissues (7)(8)(9)(10). In the central nervous system it has been shown that C3aR and C5aR are constitutively expressed by glial cells in vitro (11)(12)(13)(14) and in vivo (15) and that the expression of C3aR and C5aR is increased in inflammatory conditions (15)(16)(17).…”
mentioning
confidence: 99%